An 8-Year Retrospective Study on Suicides in Washington, DC. (March 2020) - Cuchara, Breanna; Diaz, Francisco J.
Abstract : Abstract: The suicide rate in the United States has been increasing steadily over the previous 10 years. In DC, these results are not mirrored. The suicide rate has a tendency to be lower than the rest of the country. During this retrospective review of suicides in DC, factors such as medical history and toxicology results were examined. In this study performed over 8 years (2009–2016), 394 suicides occurred. It was found that decedents committed suicide mostly by hanging (31.2%), firearms (20.3%), or drug intoxication (15.7%). The average age was 44.5 years. Similar to national statistics, male individuals committed suicide at a higher rate (77.9%) than did female individuals (22.1%). The toxicology data showed that ethanol (26.4%), antidepressants (20.1%), opioids (14.9%), and benzodiazepines (12.9%) were the drugs most frequently involved, although the finding of no drugs was most common (33.7%). Ethanol was present in 5 methods of suicide that include death by hanging, drowning, firearm, suffocation, and poisoning. This research provides information that may be useful for public health officials when confronting the issue of suicide. It is hoped that it will encourage other medical examiner offices to perform toxicological analysis and autopsy of all suicide cases.